2023
DOI: 10.3390/ijms24098414
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Relationship between Systemic Immune-Inflammation Index and Metabolic Syndrome in Children with Obesity

Abstract: Childhood obesity represents a worldwide concern as many countries have reported an increase in its incidence, with possible cardiovascular long-term implications. The mechanism that links cardiovascular disease to obesity is related to low-grade inflammation. We designed this study to investigate the diagnostic utility of inflammatory indices (NLR, neutrophil-to-lymphocyte ratio; PLR, platelet-to-lymphocyte ratio; SII, systemic immune-inflammation index; SIRI, systemic inflammation response index) in obese ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 114 publications
1
21
0
Order By: Relevance
“…Nicoară et al. 17 found that children with MetS have higher levels of inflammatory status (systemic immune-inflammation index and/or SIRI). Elevated inflammatory indices are significantly correlated with the presence and severity of MetS, which is consistent with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Nicoară et al. 17 found that children with MetS have higher levels of inflammatory status (systemic immune-inflammation index and/or SIRI). Elevated inflammatory indices are significantly correlated with the presence and severity of MetS, which is consistent with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Various complete blood count (CBC)-derived in ammatory indices such as neutrophil-lymphocyte ratio (NLR) (Lou et al, 2015), plateletlymphocyte ratio (PLR) (Atak et al, 2019), monocyte-lymphocyte ratio (MLR) (Alfhili et al, 2022), and systemic immune-in ammation index (SII) (Nicoară et al, 2023) have been used in estimating chronic low-grade in ammation in insulin resistance. The role of PIV has been wellelucidated in cancer as a biomarker to determine prognosis and survival outcomes (Fucà et al, 2020;Guven et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The different definitions used to diagnose MetS in children and adolescents create a flaw in our meta-analysis. There is no international general agreement regarding the defini-tion of this pathology, with recent evidence reporting over 40 definitions recommended by various organizations and authors deriving from criteria used in adults [4,68,69]. Even though the criteria are based on the same five components (obesity, raised triglycerides, low HDL-C, high systolic or diastolic blood pressure, and altered plasma glucose) [70], the slightly different cutoff points for each of them make it difficult to obtain highly relatable data.…”
Section: Discussionmentioning
confidence: 99%